ANALYSIS OF PURCHASING PURCHASE DECISION ON CUSTOMER SATISFACTION IN STRAWBERRY GARDENS IN BANYUROTO VILLAGE - Lola Choirunisa; Danang Manumono (JURNAL ILMIAH AGRITAS, 2018)
This study aims to determine the effect of the purchasing decision process, namely problem recognition (X1), information retrieval (X2), purchasing decisions (X3) and post-purchase behavior (X4) on customer satisfaction. The research was carried out in strawberry gardens in Banyuroto Village, Sawangan District, Magelang Regency. Sampling using Accidental Sampling method involving 40 respondents and the analytical method used is multiple linear analysis. The results of the statistical test show that problem recognition variables and purchase decision variables have a significant and significant effect on satisfaction with probability values smaller than âˆ (0.05), while information search variables and behavioral variables after purchase are at a probability level greater than âˆ (0 , 05) which means not significant to customer satisfaction.